Repair of Fractures of the Lateral Aspect of the Humeral Condyle in Skeletally Mature Dogs with Locking and Non-Locking Plates - Eayrs, Matthew K.; Guerin, Vincent; Grierson, James; Moores, Andrew P. (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to report the functional outcome and complications following transcondylar screw and epicondylar plate fixation of skeletally mature dogs with fractures of the lateral aspect of the humeral condyle using a string of pearls, limited contact dynamic compression plate (LC-DCP) or locking compression plate (LCP).Study Design This study was a retrospective review of clinical records, radiographic images and canine brief pain inventory evaluation with a supplementary non-validated questionnaire.Results Thirty-one fractures in 29 dogs were included. The majority of dogs were Spaniels (23/29). Thirty fractures had evidence of humeral intracondylar fissure. Sixteen fractures had string of pearls, eight LCP and seven LC-DCP. There were two minor complications and three major complications. Perioperative (median: 6 weeks, range: 6–12) outcome was considered fully functional for 24 fractures and acceptable for 6 fractures. One dog had an unacceptable outcome due to the failure of an LCP that healed following revision surgery. Fractures with radiographic follow-up had a persistent visible intracondylar fracture line in 20/26. Twenty-six of twenty-seven owners perceived an excellent outcome (median: 135 weeks, range: 25–246).Conclusion Repair of fractures of the lateral aspect of the humeral condyle with a transcondylar screw and epicondylar plate has a good perioperative, mid- and long-term outcome with 10% major complication rate, despite incomplete or non-union of the intracondylar fracture in 20/26 elbows.
Keywords: humeral; condylar; fracture; dog; plate